2017
DOI: 10.1021/acs.energyfuels.7b01022
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Analysis of the Composition of an Oil/Water Interfacial Film

Abstract: Interfacial tension plays an important role in reservoir mechanisms and in the production and processing of crude oil with coproduced water. Natural surfactants adhere to the oil/water (O/W) interface, which reduces the interfacial tension and in some cases leads to a solidified interfacial film with a significant impact on emulsion stability. These technical challenges are a result of the chemistry of the petroleum system, and hence optimization of production depends on a better understanding of this. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…This region indicates the absence of amine (-NH 2 ) groups in the interfacial films and the presence of a broad peak at 3200 cm −1 , representing the O-H group in carboxylic acids. This observation is consistent with similar observations in the literature Andersen et al (2017).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This region indicates the absence of amine (-NH 2 ) groups in the interfacial films and the presence of a broad peak at 3200 cm −1 , representing the O-H group in carboxylic acids. This observation is consistent with similar observations in the literature Andersen et al (2017).…”
Section: Resultssupporting
confidence: 94%
“…In addition, the peak at 1027 cm −1 indicates the accumulation of sulfoxide groups at the interface. All these demonstrate that the key contributor to the formation of the interfacial films are Polar aromatic groups with long chains and not the highly condensed aromatic groups (Andersen et al, 2017). The effect of sodium chloride.…”
Section: Resultsmentioning
confidence: 91%
“…Intuitively, one may also assume that the activity of the asphaltene constituents may vary broadly. Recently, Andersen et al 33 have confirmed that only specific types of asphaltenes are found at the interfaces, which means some types of asphaltenes are less surface-active and therefore also easily excluded.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The adsorption and positioning of natural asphaltene molecules at interfaces have been debated from having large aromatic cores parallel to interfaces to molecules positioned perpendicular to the interface. , Some of this apparent discrepancy is mainly due to the large geochemical variability in composition, molecular structure, and the observation that the molecular nature of adsorbed asphaltenes is different from the asphaltenes in bulk . Much interpretation has been based on interfacial tension analysis using the Gibbs–Langmuir approach estimating an average occupied area/molecule and the analogy with simple molecules .…”
Section: Resultsmentioning
confidence: 99%
“…6,40 Some of this apparent discrepancy is mainly due to the large geochemical variability in composition, molecular structure, and the observation that the molecular nature of adsorbed asphaltenes is different from the asphaltenes in bulk. 41 Much interpretation has been based on interfacial tension analysis using the Gibbs−Langmuir approach estimating an average occupied area/molecule and the analogy with simple molecules. 42 The latter may, even for simple molecules, show that simple polyaromatics are not adsorbed with the aromatic sheet parallel to the water−oil interface but is positioned in some angular ordered fashion.…”
Section: Xps Of Adsorbed Asphaltenes On C12 and Coohmentioning
confidence: 99%